Risiko Ketidakpastian Durasi dengan Metode PERT pada Pekerjaan Struktur Atas Proyek Gedung Bertingkat - Alfira Dwi Karimah; Lila Ayu Ratna Winanda; Munasih Munasih; Mohammad Erfan (Universitas Batanghari Jambi, 2026)
Uncertainty in duration often occurs in superstructure work due to the interdependence of activities and dynamic changes in field conditions. Deterministic scheduling methods such as the Critical Path Method (CPM) are considered incapable of representing duration variations realistically, thus requiring a probabilistic scheduling approach. Therefore, this study aims to analyze the duration of superstructure work using the Program Evaluation and Review Technique (PERT) method supported by scheduling using Microsoft Project software. The PERT method was applied through three time estimates, namely optimistic time, most likely time, and pessimistic time, with data obtained through interviews and questionnaires with experienced experts in the field of construction. Based on the analysis results, the actual duration of the project implementation reached 487 days, while the expected duration based on the PERT method was 235 days with a Z-score value of 9.79, resulting in a 47% probability of completion within the expected duration. The significant difference between the ideal duration and the actual conditions in the field indicates a 53% risk of delay that must be faced by the implementer, so that the results of this study can be used as a basis for consideration in determining a more realistic and tolerable project duration. More accurate time planning can be achieved by reducing the risk of delays through controlling and accelerating critical path activities, thereby optimizing the chances of project completion.